The Influence of Socioeconomic Trends and Experiences on Individual Perception of Corruption: The Case of Croatia. (1st October 2016) - Zakaria, Patty
Abstract : Can socioeconomic factors, experiences, or attitudes influence an individual's perception of corruption in Croatia? The aim of the present study is to examine the various micro-level factors that determine corruption perceptions. Using original survey data collected between October 2012 and June 2013, this study found that selected socioeconomic factors and experiences had a significant influence on individual-level perceptions of corruption regarding the courts, police, political systems, politicians, and political parties. This exploratory research should be followed by more precise studies in order to examine whether these results can be generalized to other cases.